Pengeloaan Keuangan di Era Digitalisasi Pada Mahasiswa Fakultas Psikologi Universitas Setiabudi Surakarta - Pramayuda, Agung; Ningrum, Retno Widya; Musadat, Irfan Achmad (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2024)
Good financial management is the key to achieving financial stability and realizing financial goals, by managing finances effectively. Financial management can be adapted to the current conditions of financial digitalization. Financial digitalization can refer to the use of digital technology in the financial industry which has now become a rapidly growing trend in Indonesia. Financial digitalization has great potential to increase access to financial services, simplify financial transactions, and encourage economic growth. By overcoming various existing challenges and risks, financial digitalization can be an effective tool for improving the welfare of Indonesian society. The method in this research uses PAR (Participatory Action Research) methodology with the aim of producing new knowledge in the context of solving problems or improving problem solving in practical life. The results of this PkM activity regarding financial management in the era of digitalization enable students from the Faculty of Psychology at Setia Budi University to know the basics of financial management, challenges in financial management, and the role of technology in financial transformation.